Volume 5: Heat Transfer, Parts a and B 2011
DOI: 10.1115/gt2011-45920
|View full text |Cite
|
Sign up to set email alerts
|

Conjugate Heat Transfer Analysis for a Film-Cooled Turbine Vane

Abstract: A conjugate heat transfer analysis methodology has been defined and applied to an Air Force film cooled turbine vane consisting of 648 cooling holes. An unstructured computational mesh was used to model both the fluid and metal sides of the turbine vane. A summary of the numerical methods employed by Code Leo is provided along with a description of the coupling procedure employed between the fluid and heat conduction computations. Numerical simulations were conducted at multiple mesh resolutions to assess accu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 0 publications
0
23
0
Order By: Relevance
“…Recently, CHT analysis has been commonly applied to predict the real metal surface temperatures and cooling performances of turbine vanes. In the numerical investigations of previous works [15][16][17][18], CHT analysis was used to study the film cooled vanes without TBC. Using a Mark II vane provided by Hylton et al [19], Bohn and Becker [20] used 3D CHT analysis and a BaldwinLomax turbulence model [21] to study the aerodynamic and thermal effects of the vane without and with TBC (ZrO2, 0.3 mm thickness).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, CHT analysis has been commonly applied to predict the real metal surface temperatures and cooling performances of turbine vanes. In the numerical investigations of previous works [15][16][17][18], CHT analysis was used to study the film cooled vanes without TBC. Using a Mark II vane provided by Hylton et al [19], Bohn and Becker [20] used 3D CHT analysis and a BaldwinLomax turbulence model [21] to study the aerodynamic and thermal effects of the vane without and with TBC (ZrO2, 0.3 mm thickness).…”
Section: Introductionmentioning
confidence: 99%
“…The present study deals with the heat transfer and fluid flow models of hot section technology relevant to gas turbines in power generation. Conjugate heat transfer models, unsteady convective models, unsteady convective models (with time‐averaged and time‐dependent parameters), and reduced order lumped capacitance thermal network method are discussed in detail under first principle modelling . Basically, first principle modelling is conducted by analysing the physical relationships of heat transfer and thermodynamics.…”
Section: Discussionmentioning
confidence: 99%
“…Dawes et al [6][7][8] developed an automated, unstructured-grid generation procedure using an octree-based cut-Cartesian method with a level-set geometry representation. Ni et al 9 demonstrated an unstructured-grid octree grid generation approach for turbine conjugate heat transfer simulation. For non-linear fluid/structure interaction applications of compressors, Ramakrishnan et al 10 , Gottfried and Fleeter 11 , and Im and Zha 12 used simple algebraically generated grids for the solid airfoils that were point-matched to multi-block grids for the passage flow.…”
Section: Introductionmentioning
confidence: 99%